Prevalence of osteoarthritis in patients at a dental school clinic and its relationship with DTM (Research, Society and Development, 2020)
Osteoarthritis (OA) represents a destructive process by which the articular bone surfaces of the condyle and joint fossa become altered. It is considered as a response of the body to increase the load on joint structures. Through the application of a structured questionnaire, the objective of this work was to evaluate the prevalence of patients with osteoarthritis, who were treated at the Unipar Dental Clinic in Cascavel, to relate to TMJ changes and to describe how a dental surgeon should treat this inflammatory joint disorder. Of the 880 volunteers, 60.4% (n = 531) did not present systemic alterations, 39.6% (n = 349) presented systemic alterations, of which 38 individuals had systemic joint alterations. It can be concluded that the dental surgeon should be aware of the symptoms of this inflammatory joint disorder in order to diagnose it early, avoiding the need for a more invasive treatment, besides knowing that the drug used may cause adverse effects.